Comparative Analysis of Students’ Perceptions in Modular Distance Learning Approach Versus Face-to-Face Learning Approach of Mindanao State University – Sulu - Salamuddin, Altamir A. (Open Access Indonesia Journal of Social Sciences, 2021)
Teaching approach gives significant to the teaching-learning process for both teachers and students. Thus, the students’ learning depends on what the school’s application of most effective and attainable teaching approach especially in the time of covid-19 pandemic. With the implementation of the new normal education, the difficulties encountered among stakeholders because of an alternative learning delivery – modular distance learning being applied in order to facilitate and to continue to serve the good education in different schools in the country Philippines. With this, the study sought to determine the perceptions of the students in Mindanao State University –Sulu regarding their experiences during face-to-face learning approach and modular distance learning approach, to ascertain the factors that can affect face-to-face learning and modular learning as perceived by the students of Mindanao State University-Sulu. This also aimed to find out the significant difference of students’ perceptions in the two learning approach. This study utilized random sampling technique through launching a survey questionnaire in assessing the perceptions of the students in Mindanao State University –Sulu by at least ten percent of the total number of enrollees from the seven departments existing in the university campus academic year 2020-2021. The findings of this study revealed that students agreed that face-to-face learning approach gives significant and had much contribution to their learning while they have disagreed on modular distance learning approach. They also believed that there are factors can affect their learning either in face-to-face and during modular learning. There is a significant difference of students’ perceptions in face-to-face learning approach and modular distance learning approach that resulted to the rejection of the null hypothesis. This study recommended that principal/director should encourage and motivate the subordinates to achieve a certain task for the good of their school. He/she should conduct an orientation program to inform parents that they are partners of teachers in education in time of crisis. Principal/director should also be responsible for interacting with teachers, representative of other school, and other stakeholders to acquire the various materials and resources for the teachers and students. There should be a training/seminar programs for the benefits of his/her subordinates in achieving school’s goals. He/she should also give clear instructions to the teachers, parents that their primary role during Modular is to establish a connection and guide the students. Lastly, he/she should encourage teachers to adopt modular even during face-to-face classes.